As maras e pandillas no Triângulo Norte da América Central e a atuação dos Estados Unidos em seu combate - Correa, Paulo Mortari Araujo (2015)
Maras and pandillas are terms usually employed in El Salvador, Guatemala and Honduras which jointly comprise the so-called Central America Northern Triangle with regard to street gangs, whose members are traditionally youngsters (and mostly men) and share a common identity, which can range from the use of specific forms of communication and cultural expression (including slangs, body gestures, tattoos, graffiti on walls and musical rhythms) to the enforcement of rigorous standards of conduct. The expansion of these groups throughout the region, and its accountability for the growth of violence in big cities have been prompting the adoption of not only domestic measures, but also international ones, which consequently involves both Central American authorities and institutions from other countries, such as the United States. Based on this finding, it is questioned, in this research, what the interest of the United States is in combating street gangs out of its borders, considering that this is commonly seen as a public security problem concerning the state in which territory such groups operate. Through the hypothetical-deductive method, and by the consultation with official reports and other American governmental sources besides the specific literature on gangs in the Northern Triangle and on the recent history and current context of the region , at least four hypothesis are tested, which refer to the United States possible perception that the gangs I) are (or are willing to be) tied to groups seen as terrorists; II) have a significant participation on the international illicit drug trade, even in collaboration with great cartels of the region; III) are transnational organized crime groups, capable of coordinating crimes on American soil with their peers established there; and that IV) the violence concerning gangs in El Salvador, Guatemala and Honduras feeds migratory fluxes (including the migration of mareros and pandilleros) from these countries towards the United States, something which would not be desired by the latter. Discussions on new and newest wars, in the context of the expansion of the International Security Studies, are adopted as the theoretical framework, especially in reference to the performance of states in the combat of non-traditional threats